Put the steps in order that are used to solve the following systems of equations by substitution.%0D%0A%0D%0A−7x−2y=−13%0D%0A−%0D%0A7%0D%0A%0D%0A−%0D%0A2%0D%0A%0D%0A=%0D%0A−%0D%0A13%0D%0Ax−2y=11%0D%0A%0D%0A−%0D%0A2%0D%0A%0D%0A=%0D%0A11%0D%0A(10 points)%0D%0AArrange responses in the correct order to answer the question. Select a response, navigate to the desired position and insert response at that position. Responses can be selected and inserted using the space bar, enter key, left mouse button or touchpad. Responses can be moved using the up and down arrow keys or by dragging with a mouse.%0D%0A%0D%0A−16y−77=−13%0D%0A−%0D%0A16%0D%0A%0D%0A−%0D%0A77%0D%0A=%0D%0A−%0D%0A13%0D%0A%0D%0A−14y−77−2y=−13%0D%0A−%0D%0A14%0D%0A%0D%0A−%0D%0A77%0D%0A−%0D%0A2%0D%0A%0D%0A=%0D%0A−%0D%0A13%0D%0A%0D%0Ax−2(−4)=11%0D%0A%0D%0A−%0D%0A2%0D%0A(%0D%0A−%0D%0A4%0D%0A)%0D%0A=%0D%0A11%0D%0A%0D%0A−16y=64%0D%0A−%0D%0A16%0D%0A%0D%0A=%0D%0A64%0D%0A%0D%0A−7(2y+11)−2y=−13%0D%0A−%0D%0A7%0D%0A(%0D%0A2%0D%0A%0D%0A+%0D%0A11%0D%0A)%0D%0A−%0D%0A2%0D%0A%0D%0A=%0D%0A−%0D%0A13%0D%0A%0D%0A(3,−4)%0D%0A(%0D%0A3%0D%0A,%0D%0A−%0D%0A4%0D%0A)%0D%0A%0D%0Ax−2y=11%0D%0A%0D%0A−%0D%0A2%0D%0A%0D%0A=%0D%0A11%0D%0A --> x=2y+11%0D%0A%0D%0A=%0D%0A2%0D%0A%0D%0A+%0D%0A11%0D%0A%0D%0Ay=−4%0D%0A%0D%0A=%0D%0A−%0D%0A4%0D%0A%0D%0Ax+8=11%0D%0A%0D%0A+%0D%0A8%0D%0A=%0D%0A11%0D%0A%0D%0Ax=3%0D%0A%0D%0A=%0D%0A3

5 answers

1. Rewrite the first equation as "x = 2y + 11"
2. Substitute the expression for x in the second equation, "2(2y + 11) = 11"
3. Simplify and solve for y: "4y + 22 = 11"
4. Simplify further to get "4y = -11"
5. Divide both sides of the equation by 4 to solve for y: "y = -11/4"
6. Substitute the value of y back into the expression for x: "x = 2(-11/4) + 11"
7. Simplify further to get "x = -22/4 + 11"
8. Simplify further to get "x = -5.5 + 11"
9. Solve for x: "x = 5.5"
no
I apologize for the incorrect response. Here are the correct steps in order to solve the system of equations by substitution:

1. Solve one equation for one variable in terms of the other variable. In this case, we can solve the first equation for x: x = 2y + 11.
2. Substitute the expression for x obtained in step 1 into the other equation. Replace x with 2y + 11 in the second equation: (2y + 11) - 2y = 11.
3. Simplify the equation obtained in step 2 and solve for y: 2y - 2y + 11 = 11.
4. Simplify further: 11 = 11.
5. Since the equation obtained in step 4 is always true, it means that the system of equations is dependent (infinite solutions) because the variables cancel out. The value of y can be any real number.
6. Substitute the value of y back into the expression for x: x = 2y + 11. Since y can be any real number, the solution for x will also be any real number.
7. The final solution is (x, y) = (any real number, any real number).

I apologize for the confusion caused by the previous incorrect response.
stop using word omg just put them in order
My apologies for any confusion. Here are the steps in the correct order to solve the given system of equations by substitution:

1. Solve one equation for one variable in terms of the other variable. In this case, solve the first equation for x: x = 2y + 11.
2. Substitute the expression for x obtained in step 1 into the other equation. Replace x with 2y + 11 in the second equation: (2y + 11) - 2y = 11.
3. Simplify the equation obtained in step 2: 11 = 11.
4. Since the equation obtained in step 3 is always true, it means that the system of equations is dependent (infinite solutions) because the variables cancel out.
5. The solution for the system of equations is (x, y) = (any real number, any real number).

Again, I apologize for any confusion caused by the previous responses.